Presymptomatic Diagnosis with MRI and Adequate Treatment Ameliorate the Outcome after Natalizumab-Associated Progressive Multifocal Leukoencephalopathy - Lindå, Hans; von Heijne, Anders (Frontiers in Neurology, 2013)
Natalizumab (Tysabri®) is a monoclonal antibody that prevents inflammatory cells from binding to brain endothelial cells and passing into the brain parenchyma. Natalizumab is a highly effective treatment for relapsing-remitting multiple sclerosis (MS). Progressive multifocal leukoencephalopathy (PML) is an opportunistic brain JC virus infection that has been shown to be associated with natalizumab treatment. We describe PML in a patient with MS after 44 monthly infusions of natalizumab. With the aid of a routine MRI scan, PML was detected before any unambiguous clinical manifestations had emerged. PML was treated with plasma exchange to accelerate removal of natalizumab. Mirtazapine and mefloquine was promptly added and approximately one month after plasma exchange, when an immune-reconstitution-inflammatory-syndrome (IRIS) appeared, steroid treatment was initiated. Steroid treatment was then continued until no virus could be detected in the cerebrospinal fluid. The outcome was favourable. We believe that this case clearly illustrates the importance of an early, presymptomatic, detection of PML and an adequate treatment. We also propose that surveillance with MRI scans, every 3 months after 24 months of treatment, should be performed in JC virus antibody positive natalizumab-treated MS patients in order to detect PML in an early phase.